The principles of blended teaching of English for Specific Purposes at engineering and pedagogical higher educational institutions - Zelenin, H. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with principles of blended learning in ESP course at engineering and pedagogical higher educational establishments, namely the scientific principle, the principles of consciousness, accessibility, activity, systematicness and consistency, the strength of knowledge and skills acquisition, visibility, the principle of taking into account the individual characteristics of students, the principle of interactivity, the principle of professional orientation, the principle of autonomy and the principle of flexibility in teaching English as a foreign language. It is shown that an ESP curriculum within a blended learning framework should be realized on the basis of active and autonomous methods of knowledge acquisition and work with information. The course is considered to be the most efficient within the framework of blended learning based upon both basic didactic regulations and methodological (general and particular) principles, considering individual student characteristics, such as age and specialization, ESP course peculiarities as well as blended learning features. The article aims to address the peculiarities of the given technology and prospects of its application for the purpose of ESP courses at engineering and pedagogical higher educational establishments. Taking into account the principles of blended ESP teaching, the following conditions of its successful application were identified: increase in the level of students’ autonomy; adaptability of the model; reasonable expenditure of classroom time and students’ independent work; individual characteristics of students; use of various means of pedagogical influence; increase in the amount of educational materials; interactivity; availability of the absolute access to educational materials.